2018
DOI: 10.1016/j.jtcme.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and hepatoprotective effects of Capparis spinosa L. fractions and Quercetin on tert-butyl hydroperoxide- induced acute liver damage in mice

Abstract: The present study investigates the antioxidant and hepatoprotective effects of Capparis spinosa L. and Quercetin in tert-butyl hydroperoxide (t-BHP) induced acute liver damage. Different fractions of C. spinosa were examined for total phenolic content and antioxidant property. Among these fractions, hydroalcoholic extract was used to assess the hepatoprotective effect in tert-butyl hydroperoxide (t-BHP) induced hepatotoxicity model by determining serum biochemical markers, sleeping time and antioxidant assay s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 42 publications
6
53
0
1
Order By: Relevance
“…Treatment with plant extract, rutin and hesperidin reduced most of the pathological alterations induced by EAC cells in mice , there is no appearance of solid carcinoma of aggregated malignant cells.As for preventive plant extract group the liver tissue showed normal hepatic parenchyma; hepatocytes, blood sinusoids, and Portal tract, While for the therapeutic plant extract group, Liver showing hepatocytes vacuolation with prepheral nucleous, the central vein is permeated with leucocytic cells . Our results showed hepatoprotective effect of C. spinosa extract were supported by the study that revealed histopathological studies under light microscope confirms the protective effects of C. spinosa and Quercetin against the t-BHPinduced liver damage [93] .…”
Section: Catalase Is a Hemoprotein And It Protects Cells From The Accsupporting
confidence: 82%
“…Treatment with plant extract, rutin and hesperidin reduced most of the pathological alterations induced by EAC cells in mice , there is no appearance of solid carcinoma of aggregated malignant cells.As for preventive plant extract group the liver tissue showed normal hepatic parenchyma; hepatocytes, blood sinusoids, and Portal tract, While for the therapeutic plant extract group, Liver showing hepatocytes vacuolation with prepheral nucleous, the central vein is permeated with leucocytic cells . Our results showed hepatoprotective effect of C. spinosa extract were supported by the study that revealed histopathological studies under light microscope confirms the protective effects of C. spinosa and Quercetin against the t-BHPinduced liver damage [93] .…”
Section: Catalase Is a Hemoprotein And It Protects Cells From The Accsupporting
confidence: 82%
“…Tesoriere et al () reported that caper bud ( C. spinosa ) contained 48.75 mg GAE/100 g. Germanò et al () determined that caper buds have number of flavonoids and other polyphenols. Total phenol contents of hydro‐alcoholic, ethyl acetate, and chloroform extracts obtained from Capparis spinosa leaves were established as 26.59 and 13.66 mg/g, respectively (Kalantari et al, ). Kalantari et al () reported that C. spinosa leave extracts contained 7.415 mg/g (hydro‐alcholic extract), 2.897 mg/g (ethyl acetate ectract), and 4.…”
Section: Resultsmentioning
confidence: 99%
“…Total phenol contents of hydro‐alcoholic, ethyl acetate, and chloroform extracts obtained from Capparis spinosa leaves were established as 26.59 and 13.66 mg/g, respectively (Kalantari et al, ). Kalantari et al () reported that C. spinosa leave extracts contained 7.415 mg/g (hydro‐alcholic extract), 2.897 mg/g (ethyl acetate ectract), and 4. 986 mg/g (chloform extract) flavonoid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on growing interest in free radical biology and the efficacy of antioxidants in protection against oxidative stress has posed interest in the use of antioxidants as a tool to prevent or decelerate the progression of oxidative stress. [12][13][14][15][16] Allium jesdianum Boiss (Allium) is the largest and most important plant genus of alliaceae family ( Figure 1) that its extract and isolated compounds possess pharmacological effects. Previous studies have indicated several biological activities for Allium species including antioxidant, antibacterial, antiviral, antiparasitic, anticarcinogenic, antifungal, anti-protozoa and antidiabetic and also effects on the cardiovascular system and treatment of common cold.…”
Section: Introductionmentioning
confidence: 99%